Genetic knockdown of Klk8 has sex‐specific multi‐targeted therapeutic effects on Alzheimer's pathology in mice. (27th January 2021) - Herring, Arne; Kurapati, Nirup K.; Krebs, Sofia; Grammon, Nils; Scholz, Luisa M.; Voss, Gerrit; Miah, Muhammad R.; Budny, Vanessa; Mairinger, Fabian; Haase, Katharina; Teuber‐Hanselmann, Sarah; Dobersalske, Celia; et al.
ABSTRACT: Aims: Previous work in our lab has identified the protease kallikrein‐8 (KLK8) as a potential upstream mover in the pathogenesis of Alzheimer's disease (AD). We showed pathologically elevated levels of KLK8 in the cerebrospinal fluid and blood of patients with mild cognitive impairment or dementia due to AD, and in brains of patients and transgenic CRND8 (TgCRND8) mice in incipient stages of the disease. Furthermore, short‐term antibody‐mediated KLK8 inhibition in moderate stage disease alleviated AD pathology in female mice. However, it remains to be shown whether long‐term reversal of KLK8 overexpression can also counteract AD. Therefore, the effects of genetic Klk 8‐knockdown were determined in TgCRND8 mice. Methods: The effects of heterozygous ablation of murine Klk8 ( mKlk8 ) gene on AD pathology of both sexes were examined by crossbreeding TgCRND8 [ hAPP +/−] with mKlk8‐ knockdown [ mKlk8 +/−] mice resulting in animals with or without AD pathology which revealed pathologically elevated or normal KLK8 levels. Results: mKlk 8‐knockdown had negligible effects on wildtype animals but led to significant decline of amyloid beta (Aβ) and tau pathology as well as an improvement of structural neuroplasticity in a sex‐specific manner in transgenics. These changes were mediated by a shift to non‐amyloidogenic cleavage of the human amyloid precursor protein (APP), recovery of the neurovascular unit and maintaining microglial metabolic fitness. Mechanistically, Klk8‐ knockdown improved Aβ phagocytosis in primary glia and Aβ resistance in primary neurons. Most importantly, transgenic mice revealed less anxiety and a better memory performance. Conclusions: These results reinforce the potential of KLK8 as a therapeutic target in AD. Abstract : We explored the effects of genetic knockdown of Kallikrein‐8 ( Klk8 ) in a mouse model of Alzheimer's disease (AD). Our results demonstrate a decline in amyloid and tau pathology as well as an improvement in neuroplasticity in a sex specific manner by interfering with amyloid precursor protein processing, restoring the neurovascular unit, maintaining microglial metabolic fitness and ultimately reducing anxiety and improving memory function. These results reinforce the potential of KLK8 as a therapeutic target in AD.